Analysis of Metals and Organics in River Water by ICP-AES and GC/MS Techniques - PATIL, A.K.; SHRIVASTAVA, V.S. (Asian Journal of Chemistry, 2010)
This work describes the detection and identification of metals and organic compounds in Tapti river water samples collected from Bhusaval, Maharashtra, India by ICP-AES and GC/MS techniques. For detection of metal HCl-HNO3 extract was prepared while organic compounds were detected in CH2Cl2 extracted mass. Also the functional groups present in organic compounds were identified by FTIR. The detection of some metals and organic compounds are found to be toxic. Beside this work, the statistical evaluations and soil and plant analysis were also carried out.